PENGUKURAN KUALITAS LAYANAN SISTEM INFORMASI AKADEMIK (SIAKAD) ITEBA MENGGUNAKAN METODE REGRESI LINIER - Nabila Tsabita; Nur Shilah; Lutfiah Nurzahra; Nasution, Nadia Widari (JURNAL SITEBA, 2023)
Academic Information Systems are often used in Institutions and Universities to manage various aspects related to academic activities. SIAKAD services refer to the various facilities and features provided by the system for various purposes such as academic administration and management needs in an educational institution. This research aims to determine the effect of SIAKAD services on user satisfaction. The calculation using linear regression method for predicting the influence of quality system to the users.